New mechanism of LncRNA: In addition to act as a ceRNA - Jiahao Zhang; Huike Zhu; Linjing Li; Yuting Gao; Boyi Yu; Guorong Ma; Xiaodong Jin; Yingbiao Sun (Non-coding RNA Research)
Long non-coding RNAs (LncRNAs) are a class of RNA molecules with nucleic acid lengths ranging from 200 bp to 100 kb that cannot code for proteins, which are diverse and widely expressed in both animals and plants. Scholars have found that lncRNAs can regulate human physiological processes at the gene and protein levels, mainly through the regulation of epigenetic, transcriptional and post-transcriptional levels of genes and proteins, as well as in the immune response by regulating the expression of immune cells and inflammatory factors, and thus participate in the occurrence and development of a variety of diseases. From the downstream targets of lncRNAs, we summarize the new research progress of lncRNA mechanisms other than miRNA sponges in recent years, aiming to provide new ideas and directions for the study of lncRNA mechanisms.